Distribution and Abundance of Copepoda in Shatt Al-Basrah Channel, Southern Iraq - Jebir et al. (Iraqi Journal of Aquaculture, 2025)
The ecology and structure of Copepoda community have been studied in two stations (S1, S2) at Shatt Al-Basrah channel: S1 was upstream the dam and S2 was down of the dam. Zooplankton samples were collected monthly for one year during the period from December 2011 until November 2012 by using Plankton net with 85 µm mesh size and 30 cm mouth aperture, by the vertical collection method. Eighteen species of copepods belonging to 15 genera were identified in the study area. In S1, there were 13 species belonging to 13 genera. However, 15 species belonging to 13 genera were recorded in S2. It was observed that the Order Calanoida was dominant in the two study areas, including 11 species, belonging to nine genera, followed by the Order Harpacticoida, which includes four species belonging to four genera, then the Order Cyclopoida, which is represented by three species belonging to two genera. The highest density of Copepoda reached 20283 ind./m3 in S2 during May 2012, whereas they disappeared in December, January, and March in S1.